Studies at the level of light, electron and fluorescence microscopy the connection of perisinusoidal cells with vitamin a metabolism in hens - Reşat Nuri AŞTI (Eurasian Journal of Veterinary Sciences)
The purpose of 'this study Was to investigate at the level of light, electron and fluorescence microscopy the connection of perisinusoidal cells with Vitamin A metabolism in hens. Thirtytwo adult Babcock toreed hens were used throughout the study. Examination of control animals' liver tissue revealed few fat storing cells carrying one or two small lipid droplets in their cytoplasms. In the animals fed with Vitamin A palmitate, lipid droplets given fluorescence against Vitamin A and reaction With 'Sudan 3 and gold chloride were observed in the cytoplasm of liver epithelial cells during the first day. Starting from second day, as lipid droplets to be found in the perisinusoidal cells and towards 15 th days they reached the maximum levels. Formations having smilar characteristics of lipid droplets were seen in dilated granuler endoplasmic sacs in the perisinusoidal cells. According to our findings, it was concluted that Vitamin A is stored as being Vitamin A ester in perisinusoidal cells of liver and these cells could have esterification activity oif Vitamin A.